The Analysis of Framing Aspect and Shot Duration Against Suspense Enhancement in Rec Film 1 of 2007 - Rita Qomariah Qomariah (ROLLING, 2022)
Abstract This research discusses the increase in suspense found in the suspense scenes in the film Rec 1 of 2007. The purpose of this research is to describe the increase in suspense through aspects of framing and shot duration in 8 suspense scenes. This research uses Noel Carroll's theory of suspense approach to reduce scene or shot that have a suspense effect, then cinematographic theory is used to read aspects of framing and shot duration in Rec 1 film. The research method used is descriptive qualitative to describe, and summarize various conditions or a situation that is in accordance with the object of research, namely Rec 1 2007 film. Researcher found 8 suspense scenes using patterns of framing aspects including dutch angle and eye level, medium shot, and long take shot.